2013
DOI: 10.1097/lbr.0b013e318282d3ca
|View full text |Cite
|
Sign up to set email alerts
|

Argon Plasma Coagulation and Electrosurgery for Benign Endobronchial Tumors

Abstract: APC is an effective method for tumor devitalization and reduction in tumor size, making it a viable and less costly therapeutic option for the treatment of benign endobronchial tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 5 publications
0
23
0
1
Order By: Relevance
“…Not only significant endobronchial tumor reduction, clinical dyspnea score and forced expiratory volume in one second (FEV1) are also improved after procedure (37). Because of the superficial effect and superiority in hemostasis, APC is usually used as a part of multi-modality approach for tumor debulking (33).…”
Section: Argon Plasma Coagulation (Apc)mentioning
confidence: 99%
See 2 more Smart Citations
“…Not only significant endobronchial tumor reduction, clinical dyspnea score and forced expiratory volume in one second (FEV1) are also improved after procedure (37). Because of the superficial effect and superiority in hemostasis, APC is usually used as a part of multi-modality approach for tumor debulking (33).…”
Section: Argon Plasma Coagulation (Apc)mentioning
confidence: 99%
“…APC is a non-contact method of electrocautery and can be introduced via both rigid and flexible bronchoscopy (33). The noncontact feature of APC allows extent and rapid coagulation, but the depth of penetration is more superficial (2-3 mm) and limited by increased tissue resistance after coagulation and desiccation (33,34).…”
Section: Argon Plasma Coagulation (Apc)mentioning
confidence: 99%
See 1 more Smart Citation
“…5,[6][7][8][9][10][11][12][13][14][15][16][17]22,[25][26][27][28][29] In the present study, the effectiveness and safety of APC and EC for treating endoluminal and mixed central airway lesions of benign and malignant causes were presented.…”
Section: Discussionmentioning
confidence: 99%
“…Effective treatment were reported in papillomatosis, hamartoma, pleomorphic adenoma, endobronchial metastases. [6][7][8][9][10][11][12][13][14][15][16]25,26,28,29 Masanori et al reported successful treatment outcomes with APC in 2 cases with post-intubation stenosis in 2006. 16 In 2012, Faguang et al also reported successful results with APC in 41 patients having endobronchial tuberculosis.…”
Section: Discussionmentioning
confidence: 99%